2007
DOI: 10.1001/archsurg.142.3.253
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Surgeon and Hospital Caseload on the Likelihood of Performing Laparoscopic vs Open Sigmoid Resection for Diverticular Disease

Abstract: High-volume surgeons and hospitals are more likely to perform laparoscopic procedures than open procedures for diverticular disease as compared with lowvolume surgeons and hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 64 publications
(83 reference statements)
2
22
0
3
Order By: Relevance
“…16,17 High-volume centers are more likely to perform laparoscopic surgery than open surgery for diverticulitis. 18 In our data, 22.7% of white patients were admitted to hospitals in the lowest quartile for hospital volume, compared with 35.1% of black patients; 18.6% of private insurance patients were admitted to these hospitals, compared with 39.6% of Medicaid patients and 34.8% of uninsured patients.…”
Section: Discussionmentioning
confidence: 51%
“…16,17 High-volume centers are more likely to perform laparoscopic surgery than open surgery for diverticulitis. 18 In our data, 22.7% of white patients were admitted to hospitals in the lowest quartile for hospital volume, compared with 35.1% of black patients; 18.6% of private insurance patients were admitted to these hospitals, compared with 39.6% of Medicaid patients and 34.8% of uninsured patients.…”
Section: Discussionmentioning
confidence: 51%
“…13 lower mortality rate, an association between hospital volume and mortality rates was not observed. Furthermore, Weber et al (15) found that diverticulosis and diverticulitis patients undergoing sigmoid colon resection were more likely to receive laparoscopic versus open sigmoid colectomies in high-volume hospitals, although a difference in mortality between the two types of surgery was not demonstrated (16). Thus, the effect of hospital volume on mortality related to surgical and medical management of diverticulitis remains unknown.…”
mentioning
confidence: 99%
“…Pacientes operados em centros de maior volume também tiveram uma chance maior (três vezes) de serem submetidos à LAP. 21 Comparando o desfecho de pacientes com diverticulite aguda complicada (n = 46) e não complicada (n = 79) submetidos à ressecção laparoscópica, um estudo observou uma taxa global de conversão de 26%, não havendo diferença estatística entre os dois grupos. A presença de cirurgia abdominal prévia foi o único fator estatisticamente significativo associado a uma maior taxa de conversão (37 vs 14%).…”
Section: Acesso Cirúrgico Na Urgênciaunclassified